2001
DOI: 10.1093/jnci/93.20.1553
|View full text |Cite
|
Sign up to set email alerts
|

 -Radiation Sensitivity and Risk of Glioma

Abstract: gamma-Radiation-induced mutagen sensitivity of lymphocytes may be associated with an increased risk for glioma, a result that supports our earlier preliminary findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
44
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(48 citation statements)
references
References 9 publications
4
44
0
Order By: Relevance
“…Enhanced G 2 chromosomal radiosensitivity has been detected in several welldefined cancer susceptibility syndromes, most notably ataxia telangiectasia [Parshad and Sanford, 2001]. Increased G 2 chromosomal radiosensitivity also has been reported in a high proportion of patients with a diverse range of cancers [Scott et al, 1994a;Parshad et al, 1996;Patel et al, 1997;Scott et al, 1999;Terzoudi et al, 2000;Bondy et al, 2001;Riches et al, 2001;Baeyens et al, 2002;Baria et al, 2002] leading to suggestions that it could be a marker of cancer predisposing genes of low penetrance whose role is to respond to DNA damage Bondy et al, 2001;Baria et al, 2002]. Support for the heritability of chromosomal radiosensitivity across generations can be inferred from family studies Scott, 2000;Curwen et al, 2005].…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced G 2 chromosomal radiosensitivity has been detected in several welldefined cancer susceptibility syndromes, most notably ataxia telangiectasia [Parshad and Sanford, 2001]. Increased G 2 chromosomal radiosensitivity also has been reported in a high proportion of patients with a diverse range of cancers [Scott et al, 1994a;Parshad et al, 1996;Patel et al, 1997;Scott et al, 1999;Terzoudi et al, 2000;Bondy et al, 2001;Riches et al, 2001;Baeyens et al, 2002;Baria et al, 2002] leading to suggestions that it could be a marker of cancer predisposing genes of low penetrance whose role is to respond to DNA damage Bondy et al, 2001;Baria et al, 2002]. Support for the heritability of chromosomal radiosensitivity across generations can be inferred from family studies Scott, 2000;Curwen et al, 2005].…”
Section: Introductionmentioning
confidence: 99%
“…In a study of head and neck cancer patients, evidence of increased G 2 chromosomal radiosensitivity was observed in young patients, thus indicating a genetic contribution to risk for early-onset cases, whereas for older patients, the proportion exhibiting enhanced sensitivity was the same as that for a normal healthy control group (Papworth et al, 2001). Using a slightly different technique, chromosomal radiosensitivity has also been reported for patients with glioma and it was suggested that the apparent broad association of mutagen sensitivity with diverse cancers indicates that multiple genes in various DNA repair pathways may be contributing to the integrated phenotype (Bondy et al, 2001). Baria et al (2002) tested the relationship between chromosomal radiosensitivity and early-onset cancer in a pilot study of patients diagnosed before the age of 20 years and found that 44% of the young cancer patients exhibited increased chromosomal radiosensitivity compared to 15 and 10% of young and adult normals, respectively.…”
mentioning
confidence: 98%
“…Although the current study and several other case-control studies have reported that various malignancies have a higher number of gamma radiationinduced chromatid breaks per cell than do controls, 14,21,22 ours is a pilot study with a relatively small number of observations and has potential confounders that were not controlled for. Previous radiation exposure is one such potential confounder.…”
Section: Discussionmentioning
confidence: 79%
“…28,29 Our results also corroborate the results of other studies in which radiation-induced mutagen sensitivity was an independent risk factor for other types of cancer. 14,21,22,30 Bondy et al 21 exposed short-term lymphocyte cultures from 219 case patients with glioma and 238 healthy controls frequency matched by age and gender to gamma radiation. They found that mutagen sensitivity was statistically significantly associated with an increased risk for glioma (OR, 2.09; 95% CI, 1.43-3.06).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation